AKTIVITAS FRAKSI ETANOL DARI EKSTRAK DAUN Peronema canescens TERHADAP TINGKAT PERTUMBUHAN Plasmodium berghei - Dhea Prasiwi; Agus Sundaryono; Dewi Handayani (ALOTROP, 2018)
[THE ACTIVITY OF THE Peronema canescens LEAVES ETHANOL EXTRACTS FRACTION AGAINST Plasmodium berghei GROWTH RATE ] The purpose of this research was to identify the secondary metabolites of compounds contained in the fraction of ethanol from leaves of Peronema canescens (Sungkai) as well as to measure the level of activity of ethanol fraction antiplasmodium leaf P.canescens against the male mice (Mus musculus) infected with Plasmodium berghei which is parasitic hemaprotozoa that can cause malaria in rodents such as rats and mice as well as molecular similarity with the parasite Plasmodium. falciparum that causes malaria in humans. The methods used in this study i.e. in maceration extraction methods to attract secondary metabolite compounds from the leaves of P.canescens followed by oil bath method to get a fraction of ethanol with the purpose of separating polar compounds from a mixture of secondary metabolite compounds contained in the sample leaf P.canescens. Assay activity against antiplasmodium males mice infected with P. berghei is done by dividing into the 5 mice group treatment i.e. Group K (-) that are quads, group K (+) given kloroquin anti malarial drug, and P1, P2, P3, which each group was given a dose of ethanol fraction from leaves of P. canescens with each dose of 0.028 (P1); 0.056 (P2), and 0.0084 g/kgBB (P3).The results of research conducted showed that administering ethanol fraction from leaves of P. canescens antimalarial activity can increase with very real on the best dose of kg BB 0084 g i.e. with the percentage inhibition of 54.06%.